FREQUENCY OF VITAMIN D DEFICIENCY IN WOMEN WITH POLYCYSTIC OVARIAN SYNDROME - Dr.Ramya Priya pojala, Dr.Aparna sarwade (South Eastern European Journal of Public Health, 2025)
BACKGROUND Polycystic ovarian syndrome (PCOS) is the most common endocrine condition characterized by polycystic ovaries, menstrual disruption, infertility, and biochemical and clinical hyperandrogenism. Vitamin D insufficiency is linked to calcium dysregulation, which triggers the development of follicular arrest in women with PCOS AIMS & OBJECTIVES Determine the incidence of vitamin D deficiency in women suffering from polycystic ovary syndrome and its correlation with other factors MATERIALS & METHODS Our patient consisted of 93 patients within the age range of 18 – 45 years who were assessed for parity, duration of PCOD, BMI and Vitamin D deficiency. Qualitative as well as quantitative analysis was carried out for factors as age, parity, Vitamin D levels, duration of PCO and BMI. All statistical analysis was carried out using SPSS software RESULTS The mean age of patients was found to be 34.36 years with mean duration of PCO being 1.54 years. 58(62.36%) of polycystic ovary syndrome women with vitamin D deficiency, wherein 26 PCOD women suffered from it for a duration of <2 years & those suffering from ≥ 2 years had 32 patients CONCLUSION A definitive relation was found between women with PCOD and Vitamin D deficiency with variable demographics playing a crucial role in their determination. Thus, we conclude that PCOS women are at a relatively high-risk to be vitamin D deficient, which requires further assessment to determine if they are at definite risk or not.